FRI0320 Disease Severity in Patients with Discoid Lupus Erythematosus from A Real-World Setting. (15th July 2016) - Hoskin, B.; Lobosco, S.; Bell, D.; Kao, A.; Hall, S.; Chen, S.-Y.
Abstract : Background: Real-world data on the severity of discoid lupus erythematosus (DLE) are scarce, limiting our understanding of the clinical course of this chronic disease that disproportionately affects minorities. Objectives: To assess the clinical burden and unmet need by disease severity in DLE patients. Methods: Data were drawn from a 2013 multinational survey of clinical practice that included 101 dermatologists across the US and EU (France, Germany, Italy, Spain & UK). Dermatologists completed the patient record (PRFs) for their next five consulting patients with cutaneous lupus erythematosus. The present analyses were a subset of patients with DLE, categorized by dermatologists into two groups based on their severity at the current visit: 1) mild, and 2) moderate/severe. The two groups were compared in bivariate analyses, using Mann-Whitney-U tests and Fisher's exact tests. Results: Final analyses included 315 DLE patients; 72% were female; mean age at diagnosis=39.7 years; mean disease duration=4.4 years. At diagnosis, 74% of DLE patients had moderate-to-severe DLE, and 10% had joints affected; at the current visit, the corresponding proportions were 27% and 11%. Among DLE patients currently presenting as moderate-to-severe, achieving remission was less common (14% vs. 60% among mild DLE patients; p≤0.0001). Patients moderate-to-severe during the present visit were more likely to be currently flaring (18% vs. 4%; p≤0.0001) or have flared in the last 12 months (37% vs. 16%; p=0.0001). Finally, dermatologist satisfaction with the level of control from treatment was also significantly lower amongst currently moderate/severe DLE patients (39% satisfied vs. 91% mild; p≤0.0001), with dermatologists reporting that better control can be achieved in over a quarter of moderate/severe DLE patients (27% vs. 3% mild; p≤0.0001). Conclusions: Across regions and despite an average of 4 years since diagnosis, a sizeable proportion of DLE patients (nearly one-third) in clinical care were moderate-to-severe at their current visit, indicating persistence, relapse or worsening. Results suggest an unmet need for better disease control. This study contributes to the scant literature on DLE by informing our understanding of the disease in real-world settings of clinical care, and may help development of appropriate new interventions amongst those not currently controlled under standard therapies. Acknowledgement: These analyses were supported by Biogen. Disclosure of Interest: B. Hoskin Employee of: Adelphi Real World, S. Lobosco Employee of: Adelphi Real World, D. Bell Employee of: Adelphi Real World, A. Kao Employee of: Employee at Biogen at the time of the research, S. Hall Shareholder of: Biogen, Employee of: Biogen, S.-Y. Chen Shareholder of: Biogen, Employee of: Biogen